'Khalas! Literature is the resistance against politics, and this is the politics of literature': an interview with Atiq Rahimi. Issue 2 (3rd April 2019) - Amiri, Lida
ABSTRACT: Atiq Rahimi is a director, photographer and translingual author who has published in Dari (Persian) and in French since 1999. As an outspoken author, Rahimi did not refrain from narrating loss, trauma and fundamentalism already in the 1990s. For his first publication in French, Syngué Sabour. Pierre de patience, he was awarded the highest literary price in France, the Prix Goncourt . With his recently published novel Les Porteurs d'eau, set in Afghanistan and Europe, Rahimi also explores challenges of the global Afghanistani diaspora. Inspired by his personal experiences of travelling from Kabul to Paris, Rahimi explores, with his Kafkaesque narratives, themes of loss, suffering and survival, all located in a war-torn country. In this interview, conducted in Paris, conversing in Persian and French, Rahimi talks about his personal journey and discusses cultural as well as literary theories. He mentions literature without borders, considers the power of literature as a means of taking a stand against political reality, learning French as a teenager and depicting strong female characters. Additionally, Rahimi explains to what extent Persian linguistics allowed him to depict the absurdity of living exile in his latest novel and ends the interview explaining the rationale behind the idea of authors without borders.